Nanoemulsion Containing Kojic Dipalmitate and Rosehip Oil: A Promising Formulation to Treat Melasma - Júlia Capp Zilles; Larissa Pedron Duarte; Thaís Carine Ruaro; Aline Rigon Zimmer; Irene Clemes Kulkamp-Guerreiro; Renata Vidor Contri (MDPI AG, 2023)
Melasma is a hard-to-treat hyperpigmentation disorder. Combined incorporation of kojic dipalmitate (KDP), the esterified form of kojic acid, and rosehip oil, an oil with antioxidant and skin-regenerating properties, into nanocarrier systems appears to be a suitable strategy to develop high-performance formulations. A high-energy method (Ultra-Turrax®) was used to develop nanoemulsions containing up to 2 mg/mL KDP, 5% rosehip oil, and 7.5% surfactant. Formulations were characterized regarding droplet size, size distribution, pH, density, morphology, KDP content, incorporation efficiency, and stability under different temperature conditions. A scale-up study was conducted. Skin permeation, antioxidant potential, and tyrosinase inhibitory activity were assessed in vitro. Cell viability studies were also performed. Results showed that nanoemulsions containing 1 and 2 mg/mL KDP had incorporation efficiencies greater than 95%, droplet size smaller than 130 nm, suitable size distribution, zeta potential of approximately −10 mV, and good stability over 30 days of refrigerated storage. The nanoemulsion containing 1 mg/mL KDP was chosen for further evaluation because it had lower nanocrystal formation, greater scale-up feasibility and allowed KDP permeation up to the epidermis similarly than observed for 2 mg/mL KDP. This formulation (1 mg/mL KDP) showed antioxidant and depigmenting efficacy, close to that of 1 mM ascorbic acid. No cytotoxicity was observed in formulations concentrations ranging from 0.06% to 1%.